2007
DOI: 10.1103/physreve.76.041909
|View full text |Cite
|
Sign up to set email alerts
|

Simple spontaneously active Hebbian learning model: Homeostasis of activity and connectivity, and consequences for learning and epileptogenesis

Abstract: As suggested by recent experimental evidence, a spontaneously active neural system that is capable of continual learning should also be capable of homeostasis of both activity and connectivity. The connectivity appears to be maintained at a level that is optimal for information transmission and storage. We present a simple stochastic computational Hebbian learning model that incorporates homeostasis of both activity and connectivity, and we explore its stability and connectivity properties. We find that homeos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…This finding has also attracted increasing theoretical and computational interest. Simple computational models have demonstrated that a branching ratio of σ = 1 indeed gives a power law size distribution, and it has the correct power of −1.5 [21,30,31]. Thus we refer to systems with σ = 1 as being at the critical point, while systems with σ < 1 are subcritical and systems with σ > 1are supercritical.…”
Section: The Critical Pointmentioning
confidence: 97%
See 4 more Smart Citations
“…This finding has also attracted increasing theoretical and computational interest. Simple computational models have demonstrated that a branching ratio of σ = 1 indeed gives a power law size distribution, and it has the correct power of −1.5 [21,30,31]. Thus we refer to systems with σ = 1 as being at the critical point, while systems with σ < 1 are subcritical and systems with σ > 1are supercritical.…”
Section: The Critical Pointmentioning
confidence: 97%
“…Each population spike represents the near simultaneous discharge of a group of local principal neurons. The exact number of neurons contributing to a given population spike is not known and is not essential to our discussion, but based on lengthscale and neuronal density estimates, this may be as high as 1000 [21]. In practice, population spikes are identified as excursions of electrode potentials that are more than 3 standard deviations above or below the mean.…”
Section: Network Activitymentioning
confidence: 99%
See 3 more Smart Citations